ANALISA RELIABILITAS DENGAN METODE DMAIC PADA UNIT EXCAVATOR ZAXIS 450LC-3 DI PT X - Muhammad Ainur Rahman; Abdul Ghofur; Akhmad Syarief (Scientific Journal of Mechanical Engineering Kinematika, 2018)
Excavator Zaxis 450LC-3 is a heavy equipment used in mining activities. The company that owns the equipment as a powerful engine will be able to carry out the operation or production to the maximum. The cause of disruption Excavator damage that often occurs is the interference with the components on multiple systems. For example undercarriage systems, electric / starting, fuel, lubrication, cooling, air intake / exhaust and so on. Thus it is necessary to study the Analysis of the Reliability Methods DMAIC In Unit Excavator Zaxis 450LC-3 at PT X, so that the operation can continue and to determine the reliability value / reliability of excavator zaxis 450LC-3. The analysis can find out the factors that influence decreasing the reliability of the unit excavator zaxis 450LC-3 with the DMAIC method and provide recommendations on the appropriate treatment plan unit zaxis 450LC-3 excavators. Following the analysis of the reliability of the DMAIC method, the reliability of the unit zaxis excavator EX1149, and EX1132 has low reliability. Resulting in lower reliability on zaxis 450LC excavator unit is due to the high frequency of unplanned break down in the system: undercarriage, hydraulic system, cooling system, electric system, and fuel system. Based on the known potential failure, the hydraulic system and engine, then do a treatment plan include: Predictive maintenance, lubrication tasks, corrective maintenance, preventive maintenance and proactive maintenance